‘I hope the doctor will send something black-or-white’. - Leif Tøfting Kongsgaard (Journal of Comparative Social Work)
The provision of public employment services to people in vulnerable life circumstances is notoriously filled with complexity and dilemmas. Not only are there multiple potential solutions to a given problem, but the very definition of the problem itself, ‘what it is all about’, is subject to interpretation and discretion. Faced with such intricacies, employment service professionals need to engage in critical reflections. Despite this recognised need, little is known about the actual processes involved in professional reflections. The aim of this article is to contribute empirically to our understanding of how professionals engage in collective reflections, specifically zooming in on the logics and reasonings behind these reflections. Drawing on ethnographic fieldwork conducted in Danish employment service organisations, the research shows that professional reflections tend to be more instrumental than critical, and more focused on certainty and what to do, than on understanding dilemmas and bringing in new perspectives on problems. Following the perspective of reparative critique, the analysis explores avenues for fostering more critical reflections within the context of public employment service. The findings bear implications for understanding the institutional and organisational embeddedness of professional reflective practices within welfare work, particularly in the realm of public work inclusion services.